THE LEGISLATION OF THE REPUBLIC OF KAZAKHSTAN IN THE FIELD OF PROTECTION OF PERSONAL DATA: A COMPARATIVE LEGAL ANALYSIS WITH THE LAW OF THE EUROPEAN UNION - Lozovaya Ольга Васильевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
This article analyzes the Law of Republic of Kazakhstan on Personal Data and it’s Protection of 21 May 2013. Author conducted a detailed comparative legal analysis of the Law and the Directive 95/46/EC of the European Parliament and of the Council of the European Union of 24 October 1995 on the protection of individuals with regard to the processing of personal data and on the free movement of such data, as well as with the same Law of the Russian Federation(in some respects) to make the informed review and add some constructive suggestions. Author emphasizes the problematic provisions of the Law and make suggestions for improvement of it.